New QC Codes over GF(11) - Daskalov, Rumen; Metodieva, Elena (2020 Algebraic and Combinatorial Coding Theory (ACCT), 2020)
A linear code of length n, dimension k and minimum distance d over GF (q) is denoted by [n, k, d] q . One of the main problem in linear coding theory is - for given length and dimension to construct codes with best possible minimum distances. In this talk we present 10 new QC codes.